2008
DOI: 10.1007/978-3-540-88643-3_10
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape of Bidirectional Model Transformations

Abstract: Abstract. Model transformations are a key element in the OMG's Model Driven Development agenda. They did not begin here: the fundamental idea of transforming, automatically, one model into another is at least as old as the computer, provided that we take a sufficiently broad view of what a model is. In many contexts, people have encountered the need for bidirectional transformations. In this survey paper we discuss the various notions of bidirectional transformation, and their motivation from the needs of soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 27 publications
0
60
0
4
Order By: Relevance
“…3), we now focus on alternative bidirectional languages that share and address similar challenges as TGGs but take fundamentally different strategies. As bidirectionality is a challenge in various application domains and communities, there exists a substantial number of different approaches, formalizations and tools [Ste08]. The lenses framework is of particular interest when compared to TGGs, as [HEO + 11] has shown that incremental TGGs can be viewed as an implementation of a delta-based framework for symmetric lenses.…”
Section: Related Work On Alternative Bidirectional Languagesmentioning
confidence: 99%
See 2 more Smart Citations
“…3), we now focus on alternative bidirectional languages that share and address similar challenges as TGGs but take fundamentally different strategies. As bidirectionality is a challenge in various application domains and communities, there exists a substantial number of different approaches, formalizations and tools [Ste08]. The lenses framework is of particular interest when compared to TGGs, as [HEO + 11] has shown that incremental TGGs can be viewed as an implementation of a delta-based framework for symmetric lenses.…”
Section: Related Work On Alternative Bidirectional Languagesmentioning
confidence: 99%
“…Unification has wide-reaching consequences including enabling a natural bootstrap and higher order transformations. Finally, TGGs served as an inspiration and basis for the standard OMG bidirectional transformation language QVT and can be regarded as a valid implementation thereof [Ste08].…”
Section: Related Work On Alternative Bidirectional Languagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Testing model transformations is not an easy task and present numerous challenges [1,2,3,4]. In the literature there are two main approaches to model transformation testing (see also Section 5).…”
Section: Introductionmentioning
confidence: 99%
“…The papers follow on from earlier work by the present author, [10], in which questions answered here, specifically the role of relation invocation in when and where clauses (relation definition applied to particular arguments), were left open. Discussion of the foundations of, and range of approaches to, bidirectionality, not specific to QVT, are presented in [9] and [8] respectively.…”
Section: Introductionmentioning
confidence: 99%